Changes in Contemporary Communication Ecosystems Ask for a “New Look” at the Concept of Mediatisation - Mazzoleni, Gianpietro (Javnost-The Public, 2017)
The concept of “mediatisation” is enjoying growing popularity in scholarly research because it provides an insight into the influence of media logics in society. This is why mediatisation has been applied to several social, cultural and political phenomena. However, its original meaning is to be re-examined vis-à-vis the establishing of new media and communication ecosystems. This article provides a concise overview of the concept’s applications in academia and probes into its real usefulness for mass and new media communication research.